Human Movement Training With a Cable Driven ARm EXoskeleton (CAREX) - Mao, Ying; Jin, Xin; Gera Dutta, Geetanjali; Scholz, John P.; Agrawal, Sunil K. (IEEE transactions on neural systems and rehabilitation engineering, 2015)
In recent years, the authors have proposed lightweight exoskeleton designs for upper arm rehabilitation using multi-stage cable-driven parallel mechanism. Previously, the authors have demonstrated via experiments that it is possible to apply "assist-as-needed" forces in all directions at the end-effector with such an exoskeleton acting on an anthropomorphic machine arm. A human-exoskeleton interface was also presented to show the feasibility of CAREX on human subjects. The goals of this paper are to 1) further address issues when CAREX is mounted on human subjects, e.g., generation of continuous cable tension trajectories 2) demonstrate the feasibility and effectiveness of CAREX on movement training of healthy human subjects and a stroke patient. In this research, CAREX is rigidly attached to an arm orthosis worn by human subjects. The cable routing points are optimized to achieve a relatively large "tensioned" static workspace. A new cable tension planner based on quadratic programming is used to generate continuous cable tension trajectory for smooth motion. Experiments were carried out on eight healthy subjects. The experimental results show that CAREX can help the subjects move closer to a prescribed circular path using the force fields generated by the exoskeleton. The subjects also adapt to the path shortly after training. CAREX was also evaluated on a stroke patient to test the feasibility of its use on patients with neural impairment. The results show that the patient was able to move closer to a prescribed straight line path with the "assist-as-needed" force field.